Exploring the interplay of choreography and singing techniques in vocal group performances at Pekan Seni Mahasiswa Nasional Competition - Akbar Bagastiar; Asnie Izzatul Anshory (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2023)
A vocal group is a group of individuals with singing skills united in one Group with different vocal voices. Several voice levels in vocal groups range from soprano, alto, tenor, and bass. In the presentation of vocal groups, two aspects need to be considered: musical and non-musical. Some examples of musical aspects that need to be considered in group vocals are intonation, timbre, dynamics, technique, and arrangement of works. Apart from that, non-musical aspects also play an essential role in the presentation of vocal groups. Some examples of musical aspects that must be considered are costumes, props, and choreography. This research discusses choreography in Partere Voce, where the choreography can influence the breathing strength of the singers, so vocal group members need specific singing techniques. The method used for this research is data collection through interviews and observations. Researchers participated in the competition activities so that they knew the field conditions and felt what was complained about; after that, the researchers tried to find the main points of the problem and solutions to the perceived problems.